(untitled) (Journal of Economic Research & Business Administration, 2016)
In article it is considered problems of effective realization of competitive strategy of holding, by means of application of functional strategy: financial and investment within which maximizing cost of the holding company is carried out. Development of strategy of management of cost of business of holding structure, has to consider that the cost of holding is formed as a result of use of all assets and financial resources including those assets which aren’t reflected in the consolidated accounting reports of holding.